Heat Transfer Enhancement from Bouncing Bubble Dynamics - ROBINSON, ANTHONY; MURRAY, DARINA; DONOGHUE, DAVID BRENDAN (My University, 2011)
Heat transfer enhancement resulting from the effects of two phase flow can play an important role in for convective cooling. Currently, the effect of bubble/surface interactions has received very little attention. To address this, this paper investigates the effect of a single bubble bouncing on a heated surface. Local heat transfer measurements have been performed for two bubble release heights of 15 and 25 mm, along with two levels of surface heat flux, 5800 W/m2 and 9040 W/m2. High-speed photography and infrared thermography have been employed to investigate the path of the bubble and the resulting heat transfer effect when an interaction between the bubble and the heated surface takes place.
Proceedings of the 6th Baltic Heat Transfer Conference
PUBLISHED
Tampere, Finland
Keywords: Thermal engineering; Smart & Sustainable Planet